Pemanfaatan Lahan Pekarangan dengan Budidaya Sayuran Organik menggunakan Greenhouse dalam Mendukung Ketahanan Pangan di Desa Ngargorejo, Boyolali - Arthalia Reginanda, Faradita; Fadhila, Nila; Wahyudi, Fariz; Yasir ‘Adn, Wildan; Zacky Yustisio, Haidar; Fadhila Naura, Alifia; Syahidah, Muthia; Virginia, Reyna; Nabila, Zahra; Widhoretno, Annasa (Eastasouth Institute, 2024)
Greenhouse is one of the KKN activities carried out in Ngargorejo Village. This activity was carried out with the aim of increasing the use of yard land through cultivating organic vegetables using greenhouse technology in Ngargorejo Village, Boyolali. Through this activity, it is hoped that better food security can be created at the household level while improving the welfare of village communities. Activities carried out include counseling, technical training, as well as building a demonstrative greenhouse. The results of this program show an increase in public awareness of the importance of using home gardens and food sustainability. Apart from that, the application of greenhouse technology has proven effective in increasing the productivity and quality of organic vegetables in the village.